Plants and water: the search for a comprehensive understanding. (23rd August 2022) - Rockwell, Fulton; Sage, Rowan F
Abstract: We learn early in life sciences classes that water is the solution of life, working in tandem with carbon to make life as we know it possible. Globally, the abundance of water can be misleading, as most of this water is unavailable, being overly salinized in the oceans or locked in deep underground reserves. On land, the critical supply is of freshwater, which is unevenly distributed in space and time. Even the wettest environments can experience episodic water deficit, and flash flooding periodically occurs in arid landscapes. While humanity can capture, store and transport freshwater over large distances to ensure sustained supply, such options are not apparent for plants except in an immediate local context. Plants must make do with the water in their immediate surroundings, whether it be abundant or scarce. How they do this has led to a myriad of adaptive solutions, involving capturing, storing and transporting water. The traits that enable them to optimize water use in a range of hydraulic environments, subject to multivariate selective constraints, are the essence of the discipline of plant–water relations.